Creativity and Decision Making in Giftedness - María de los Dolores Valadez Sierra; Celia Josefina Rodríguez Cervantes; Emilio Verche; Beatriz Verónica Panduro Espinoza (MDPI AG, 2024)
Creativity is the ability to re-experience mental representations and is the basis of intuitive thinking when constructing images prior to the elaboration of an action plan. Creativity is thought to be related to orbitofrontal functions that govern decision making, such as inhibitory control, risk-benefit evaluation and acceptance of limits and rules, given that these processes prepare one against possible scenarios. Objective: In this study, the relationship between creativity and decision making is investigated to understand the needs of gifted students. Method: A cross-sectional descriptive study was carried out with gifted students (IQ mean = 133) aged 8-10 years old (n = 25). Instruments: Creative Imagination Test (PIC) and subtests of the Neuropsychological Battery of Executive Functions and Frontal Lobes (BANFE-2) were employed. Analysis: A Spearman correlation analysis was conducted between the normalized BANFE-2 scores and the percentiles of PIC. Results: Moderate correlations were found between creative/narrative flexibility and decision making/risk percentage (r = 0.432, p ≤ 0.05) and decision making/response-effectiveness (r = 0.426, p ≤ 0.05), as well as between graphic creativity/shadow and color with decision making/response-effectiveness (r = 0.452, p ≤ 0.05) and inhibition (r = 0.673, p ≤ 0.01); moderate negative correlations were found between inhibition and graphic creativity/title (r = −0.570, p ≤ 0.05) and general graphic creativity (r = −0.489, p ≤ 0.05). Conclusions: Creativity in students with intellectual giftedness is favored by a relationship with orbitofrontal functions. Analysis of risk situations and effective decision making increase narrative creation and diminished inhibition allows for greater creative graphic production.